Risk Factors and Mortality Associated with Candida krusei Bloodstream Infections. (4th October 2017) - Kronen, Ryan; Lin, Charlotte; Hsueh, Kevin; Powderly, William; Spec, Andrej
Abstract: Background: Candida krusei (CK) candidemia is associated with high mortality, but whether this is due to underlying comorbidities in affected patients or the organism itself is unknown. We analyzed factors associated with C. krusei candidemia and its outcomes. Methods: A retrospective analysis of hospitalized patients with candidemia was conducted at our institution between 2002 and 2015. Data were collected on demographics, comorbidities, medications, procedures, central lines, vital signs, and labs. Univariable logistic and Cox regression were used to identify potential risk factors associated with CK and mortality, respectively. Multivariable analyses were then constructed parsimoniously from these variables. Results: Of 1, 873 candidemia events, 59 were due to CK. In multivariable analysis, CK candidemia was predicted by hematologic malignancy (OR 8.9, 95% CI [4.1, 19.7]), stomach cancer (OR 14.6, 95% CI [2.9, 72.5]), absolute neutrophil count (OR 2.4, 95% CI [1.2, 4.8]), and the use of prophylactic azole antifungals (OR 2.2, 95% CI [1.1, 4.3]), monoclonal antibodies (OR 5.7, 95% CI [2.0, 15.8]), and penicillin β-lactamase inhibitors (OR 2.5, 95% CI [1.3, 4.8]). The C-statistic was 0.86 (95% CI [0.81, 0.91]). The crude mortality rates were 86.4% for CK candidemia and 63.6% for non-CK candidemia. Although CK was associated with higher mortality in univariable Cox regression (Figure 1, HR 1.8, 95% CI [1.3, 2.4]), this relationship was no longer significant (HR 1.2, 95% CI [0.8, 1.7]) with the addition of the following confounders: hematologic malignancy (HR 0.9, 95% CI [0.7, 1.1]), absolute neutrophil count (HR 1.7, 95% CI [1.4, 2.2]), stomach cancer (HR 1.0, 95% CI [0.5, 1.9]), coagulopathy (HR 1.0, 95% CI [0.9, 1.2], and prophylactic corticosteroids (HR 1.4, 95% CI [1.2, 1.7] (Figure 2). Conclusion: A similar set of patient characteristics is associated with both CK infection and increased mortality, suggesting that patients with CK candidemia are at higher risk of mortality due to underlying illness rather than organism-specific mechanisms. Disclosures: W. Powderly, Merck: Grant Investigator and Scientific Advisor, Consulting fee and Research grant Gilead: Scientific Advisor, Consulting fee Astellas: Grant Investigator, Research grant A. Spec, Astellas Pharma US, Inc.: Grant Investigator, Research grant